2014
DOI: 10.5343/bms.2013.1015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating edge-of-range genetic patterns for tropical echinoderms, <I>Acanthaster planci</I> and <I>Tripneustes gratilla</I>, of the Kermadec Islands, southwest Pacific

Abstract: AbstrAct.-Edge-of-range populations are often typified by patterns of low genetic diversity and high genetic differentiation relative to populations within the core of a species range. The "core-periphery hypothesis," also known as the "central-marginal hypothesis," predicts that these genetic patterns at the edge-of-range are a consequence of reduced population size and connectivity toward a species range periphery. It is unclear, however, how these expectations relate to high dispersal marine species that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 54 publications
1
29
2
Order By: Relevance
“…This observation suggests that while surface ocean currents permit sufficient gene flow across the Pacific Ocean to ensure populations retain a high degree of connectivity, circulation patterns and IBD may also facilitate regional larval retention, that stabilises population genetic structure. Because even low levels of gene flow [101, 102] are able to prevent population divergence, it is conceivable that standing genetic diversity and structure are maintained by a “founder takes all” density-dependent effect [103], where individuals arriving after an initial colonisation event may be “blocked” by established conspecifics [11, 103]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that while surface ocean currents permit sufficient gene flow across the Pacific Ocean to ensure populations retain a high degree of connectivity, circulation patterns and IBD may also facilitate regional larval retention, that stabilises population genetic structure. Because even low levels of gene flow [101, 102] are able to prevent population divergence, it is conceivable that standing genetic diversity and structure are maintained by a “founder takes all” density-dependent effect [103], where individuals arriving after an initial colonisation event may be “blocked” by established conspecifics [11, 103]. …”
Section: Discussionmentioning
confidence: 99%
“…While several studies have examined C-M genetic patterns in terrestrial taxa [5, 10], comparatively few investigations have involved marine species [8], and marine invertebrates in particular [11]. Marine systems present several challenges for range-wide studies, as >70% of invertebrates and many vertebrates are characterised by large population sizes, high fecundity, external fertilisation and larvae that typically remain in the plankton for several weeks, although this may vary anywhere from a few minutes to years [1216].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the role of connectivity in determining heat tolerance depends on how strong a role the genetic factor plays. In addition, locations with the greatest connectivity to other reefs within a population of a species are more likely to have greater genetic diversity than more isolated locations (Liggins et al, 2014). If that genetic diversity includes different levels of adaptation to heat stress, then the bleaching response should reflect that.…”
Section: Discussionmentioning
confidence: 99%
“…All samples shows 99-100% similarity with the COI sequences of T. gratilla (accession number KF012821.1-KF012824.1.) from Southwest Pacific (Liggins et al, 2014). The data indicated that the samples were collected from Cenderawasih Bay ecoregion is T. gratilla species.…”
Section: Resultsmentioning
confidence: 87%